Tekst kao interakcija: moguće implikacije na nastavu stranih jezika (Philologia, 2021)
This paper explores some aspects of textual interaction within written discourse analysis as well as possible implications of such an approach for foreign language teaching. The focus is on writer-reader interaction. The writer guides the reader by signalling through the text, whereas the reader approaches the text actively by using the writer’s signals and intertextuality which can help create expectations on further text development. All this can have a positive influence on teaching reading and writing skills and some classroom activities are suggested at the end of the paper.